Growth and drainage of supraglacial lakes on debris mantled Ngozumpa Glacier, Khumbu Himal, Nepal - Benn, Douglas Iain; Wiseman, S; Hands, KA (2001)
Ablation of debris-mantled glaciers in Nepal has resulted in the formation of several potentially unstable moraine-dammed lakes, some of which constitute serious hazards. Ngozumpa Glacier, Khumbu Himal, has undergone significant downwasting in recent decades. and is believed to lie close to the threshold for moraine-dammed lake formation. The debris-mantled ablation area of the glacier is Studded with numerous supraglacial lakes, the majority of which occupy closed basins with no perennial connections to the englacial drainage system "perched lakes". Perched lakes call undergo rapid growth by subaerial and water-line melting of exposed ice faces, and calving. Subaerial and subaqueous melting beneath thick (>1 m) debris mantles is comparatively insignificant. Although lake expansion can contribute substantially to ablation of the glacier, perched lakes cannot continue to grow indefinitely. but are subject to rapid drainage once a connection is made to englacial conduits. The level of one of the takes on the Ngozumpa, however, is controlled by the altitude of a spillway through the lateral moraine of the glacier, This lake underwent only limited growth in the period 1998-2000, but is likely to experience monotonic growth if glacier mass balance continues to be negative.